Medication preventing postictal hypoperfusion and cognitive side-effects in electroconvulsive therapy: A retrospective cohort study - Verdijk, Joey P. A. J.; Schuur, Gijsbert; Pottkämper, Julia C. M.; ten Doesschate, Freek; Hofmeijer, Jeannette; van Waarde, Jeroen A. (Frontiers in Psychiatry, 2023)
Background Electroconvulsive therapy (ECT) is associated with postictal confusion and cognitive side-effects. In rats, acetaminophen, non-steroidal anti-inflammatory drugs (NSAIDs) and calcium antagonists decreased postictal cerebral hypoperfusion along with reduction in postictal symptoms. In this study, in ECT-patients, we explore associations between use of these potentially protective medications and occurrence of postictal confusion and cognitive outcome. Materials and methods In this retrospective, naturalistic cohort study, patient-, treatment-, and ECT-characteristics, were collected from medical files of patients treated with ECT for major depressive disorder (MDD) or bipolar depressive episode. To test for associations of use of these medications with occurrence of postictal confusion, 295 patients could be included. Cognitive outcome data were available in a subset of 109 patients. Univariate analyses and multivariate censored regression models were used to test for associations. Results Occurrence of severe postictal confusion was not associated with use of acetaminophen, NSAIDs or calcium antagonists (n = 295). Regarding the cognitive outcome measure (n = 109), use of calcium antagonists was associated with higher post-ECT cognitive scores (i.e., better cognitive outcome; β = 2.23; p = 0.047), adjusted for age (β = −0.02; p = 0.23), sex (β = −0.21; p = 0.73), pre-ECT cognitive score (β = 0.47; p < 0.0001), and post-ECT depression score (β = −0.02; p = 0.62), but use of acetaminophen (β = −1.55; p = 0.07) as well as NSAIDs (β = −1.02; p = 0.23) showed no associations. Conclusion This retrospective study does not find arguments for protective effects of acetaminophen, NSAIDs or calcium antagonists against severe postictal confusion in ECT. As a preliminary finding, the use of calcium antagonists was associated with improved cognitive outcome after ECT in this cohort. Prospective controlled studies are necessary.